Physical activity and health, parallel axises that get together in Physical Education (Original) (Revista científica Olimpia, 2021)
Apathy towards physical activity is responsible for many diseases that appear without realizing it being so lazy in front of devices or technologies that create addictions. This work reflects on the need for physical activities, knowing the benefits that contribute by not stop doing physical exercise. Proposing different physical activity programs available to interested parts through Physical Education classes for the benefit of health, whose objective is to stimulate the practice of physical activities benefiting our body?
Keywords: physical activity; physical exercise; health; program; physical condition